The Cost-Effectiveness of Human Immunodeficiency Virus Testing and Treatment Engagement Initiatives in British Columbia, Canada: 2011–2013. (26th September 2017) - Nosyk, Bohdan; Min, Jeong E; Krebs, Emanuel; Zang, Xiao; Compton, Miranda; Gustafson, Reka; Barrios, Rolando; Montaner, Julio S G; ,
Abstract : We used a dynamic human immunodeficiency virus (HIV) transmission model to determine the cost-effectiveness of HIV care interventions in British Columbia, Canada, in 2011–2013. HIV testing and treatment initiation interventions were cost-effective, while the treatment retention intervention was not. Abstract: Background: Recognition of the secondary preventive benefits of antiretroviral therapy (ART) has mobilized global efforts to "seek, test, treat, and retain" people living with human immunodeficiency virus [HIV]/AIDS (PLHIV) in HIV care. We aimed to determine the cost-effectiveness of a set of HIV testing and treatment engagement interventions initiated in British Columbia, Canada, in 2011–2013. Methods: Using a previously validated dynamic HIV transmission model, linked individual-level health administrative data for PLHIV, and aggregate-level HIV testing data, we estimated the cost-effectiveness of primary care testing (hospital, emergency department [ED], outpatient), ART initiation, and ART retention initiatives vs a counterfactual scenario that approximated the status quo. HIV incidence, mortality, costs (in 2015CDN), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios were estimated. Analyses were executed over 5- to 25-year time horizons from a government-payer perspective. Results: ED testing was the best value at 30216 per QALY gained and had the greatest impact on incidence and mortality among PLHIV, while ART initiation provided the greatest QALY gains. The ART retention initiative was not cost-effective. Delivered in combination at the observed scale and sustained throughout the study period, we estimated a 12.8% reduction in cumulative HIV incidence and a 4.7% reduction in deaths among PLHIV at 55258 per QALY gained. Results were most sensitive to uncertainty in the number of undiagnosed PLHIV. Conclusions: HIV testing and ART initiation interventions were cost-effective, while the ART retention intervention was not. Developing strategies to reengage PLHIV lost to care is a priority moving forward.